2006
DOI: 10.1159/000097383
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Vitamin D and Haemostatic Factors in Healthy Subjects: The Tromsø Study

Abstract: Background: Receptors for vitamin D have been found in various tissues, including the vascular endothelium. The role of vitamin D in the haemostatic process is uncertain, but in vitro studies may indicate a pro-fibrinolytic effect. Methods: Two hundred and six subjects (105 males) were included in the study. The relations between indices of calcium metabolism and haemostatic factors [tissue plasminogen activator antigen (tPA Ag), plasminogen activator inhibitor 1 (PAI-1), prothrombin fragment 1+2, activated fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 44 publications
3
37
0
Order By: Relevance
“…High PAI-1 concentrations are an independent risk factor for recurrence of a heart attack before the age of 45 years [36], and 1,25(OH) 2 D reduces PAI-1 concentrations in vascular and smooth muscle cells [37,38]. Our study showed a trend for the highest PAI-1 concentrations among subjects in the lowest third of vitamin D status, which is in agreement with the results of Jorde et al [39] who suggested a role for vitamin D in fibrinolysis and maintenance of the integrity of the vascular endothelium. Although we observed no association between s25(OH)D concentration and IL-6, we did observe a positive association between iPTH and IL-6.…”
Section: Discussionsupporting
confidence: 92%
“…High PAI-1 concentrations are an independent risk factor for recurrence of a heart attack before the age of 45 years [36], and 1,25(OH) 2 D reduces PAI-1 concentrations in vascular and smooth muscle cells [37,38]. Our study showed a trend for the highest PAI-1 concentrations among subjects in the lowest third of vitamin D status, which is in agreement with the results of Jorde et al [39] who suggested a role for vitamin D in fibrinolysis and maintenance of the integrity of the vascular endothelium. Although we observed no association between s25(OH)D concentration and IL-6, we did observe a positive association between iPTH and IL-6.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the relationship between leptin and vitamin D and its clinical importance warrant further research. High sensitivity C-reactive protein (hsCRP) levels have been shown to correlate negatively with 1,25(OH) 2 D 3 concentration in healthy individuals [330], a finding supporting the anti-inflammatory effects of vitamin D. However, vitamin D supplementation did not alter hsCRP or cytokine levels [330,331].…”
Section: Obesitymentioning
confidence: 97%
“…Observational studies have generated conflicting results. Some cross-sectional studies indicate that hypovitaminosis D is associated with higher serum levels of inflammatory biomarkers, such as IL-6, TNF-α, and C-reactive protein (CRP), in healthy [38,39,40,41] and in obese subjects [42], while others could not confirm these findings [43,44,45,46]. Given the observational design, cross-sectional studies cannot prove causality or fully discount residual confounding by unmeasured variations.…”
Section: Vitamin D and Inflammationmentioning
confidence: 99%